Understanding of halal certification with halal purchasing decision of Muhammadiyah Surabaya MSMEs: Analytical descriptive study - Anas, Muhammad; Saputro, Andre Ridho; Latifah, Luluk (Universitas Ahmad Dahlan, 2025)
Public awareness of the importance of halal certification is increasing. Halal certification is not only a guarantee of the halalness of a product, but also a determining factor in consumer decision-making. The supply chain is an important element in meeting human needs. Consciously or not, the supply chain is an inseparable part of daily activities. Therefore, many companies compete to meet the needs of the supply chain through various product innovations. This study aims to analyze the understanding of Muhammadiyah Surabaya MSME actors regarding halal certification and how it affects the decision to purchase halal raw materials. With a descriptive-analytical approach, this study is expected to provide an in-depth picture of the relationship between the level of understanding of halal certification and the practice of purchasing halal raw materials. As many as 66% of MSMEs still choose halal-certified suppliers even though raw materials are more expensive. This decision reflects the priority on halal values as a moral foundation and long-term business strategy to build reputation and consumer loyalty. As many as 76% of respondents prefer halal suppliers even though they are farther away. The halal aspect is a top priority compared to logistics efficiency, with a commitment to maintaining the quality and halalness of products throughout the supply chain. As many as 93% of respondents said that promotions carried out by halal suppliers influenced their decisions. This emphasizes the importance of effective marketing strategies in building trust and strengthening the image of halal suppliers in the eyes of business actors. Keywords: Consumer behavior, Halal certification, Halal logistics, MSMEs, Raw materials, Supply chain.